2017
DOI: 10.1021/acs.jpcb.7b03835
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Particles Selectively Confined in the Mesoporous Channels of SBA-15 Yielding a Very Stable Catalyst for DRM Reaction

Abstract: A series of four Ni catalysts supported on SBA-15 and on a high SiO surface area have been prepared by modified impregnation (ImU) and deposition-precipitation (DP) methods. The catalysts have been extensively characterized, including in situ XAS (bulk sensitive) and XPS (surface sensitive) techniques, and their catalytic activities evaluated in the dry reforming reaction of methane (DRM). The combined use of XPS and XAS has allowed us to determine the location of nickel particles on each catalyst after reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Accordingly, an intimate contact between ceria and the active metal phase (coke promoter) should facilitate the process, and this can be addressed by using a high surface support [32–34] . On the other hand, a proper dispersion of the active metal phase has been shown to reduce graphitic coke formation by suppressing methane decomposition (the main source of coke at high temperatures), [35,36] a structure‐sensitive reaction which is favored in larger crystal [37,38] . In this sense, several approaches has been explored to prevent metal aggregation as MgO‐based solid‐solution catalysts, [39–41] mixed metal oxide materials (as perovskites), [42,43] or co‐impregnation with promoter oxides [44–46] …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, an intimate contact between ceria and the active metal phase (coke promoter) should facilitate the process, and this can be addressed by using a high surface support [32–34] . On the other hand, a proper dispersion of the active metal phase has been shown to reduce graphitic coke formation by suppressing methane decomposition (the main source of coke at high temperatures), [35,36] a structure‐sensitive reaction which is favored in larger crystal [37,38] . In this sense, several approaches has been explored to prevent metal aggregation as MgO‐based solid‐solution catalysts, [39–41] mixed metal oxide materials (as perovskites), [42,43] or co‐impregnation with promoter oxides [44–46] …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tomographic study showed that Ni 0 particles in Ni works [31][32], the preparation method described here, for the stabilization of nickel, is simpler (no need of promoters) and leads to smaller Ni NPs resulting in better catalytic performances. It has also to be noted that, among a lot of studies (more than 100 papers) dealing with Ni/silica catalysts in DRM, very few (see Table S1) used Ni silica-based catalysts working with a GHSV ≥ 144 L g -1 h -1 [33][34][35]. Hence, clearly Ni 0 aq.coll/S can be qualified as one of the best Ni/silica-based catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Fine‐size metal nanoparticles can be dispersed on the surface of thermally stable oxide powders to prevent the sintering caused by coalescence of contacting metal nanoparticles at high temperatures, improving the thermal stability of the catalyst. [ 44–46 ] The reduced possibility of sintering is ascribed to the good separation of individual metal nanoparticles on the support oxides and the low mobility of metals in the gaseous phase. Moreover, many oxide supports can exhibit Lewis acidity/basicity and even chemical reactivity to strongly interact with both reactant species and metal catalyst nanoparticles, resulting in a change of the catalytic activity.…”
Section: Typical Metal Catalysts For Light‐driven Drm Processmentioning
confidence: 99%